PENGARUH INVESTASI SEKTOR PRIMER TERHADAP PERTUMBUHAN EKONOMI DAN PENYERAPAN TENAGA KERJA DI PROVINSI KALIMANTAN TIMUR - Rahcmad Budi Suharto; Diana Lestari; Awaluddin Awaluddin (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2023)
Economic growth is a country’s economic problem in the long term. Relatively high economic growth will greatly affect the level of poverty, because with a growing economy there will be a lot of production of goods and services produced by a region, which in turn will absorb labor, so that the income per capita of the population is higher which in turn will reduce poverty in an area. The method used in this study is quantitative data analysis method and data analysis method using path diagrams with 6 measurement dimensions, namely, PDRB, Government Expenditures, General Allocation Funds, Special Allocation Funds, Economic Growth and Poverty Rates in East Kalimantan Province in 2009-2020. All independent variables in this study have a positive and significant effect on economic growth, while all independent variables in this study have a non-significant effect on the poverty variable, this is because East Kalimantan Province has a fairly high social inequality in the last 5 years.